Predicting the Potential Distribution of Major Malaria Vectors Based on Climate Changes in Sistan and Baluchistan Province, Southeastern Iran - Jalil Nejati; Hassan Vatandoost; Mehdi Zanganeh Baygi; Ahmad Ali Hanafi-Bojd (Journal of Arthropod-Borne Diseases, 2022)
Background: Given the significance of climate change and its substantial effects on mosquitoes’ habitats, this study was aimed to model the spatial distribution of the main malaria vectors in the south east of Iran.